Hydrothermal growth and scintillation properties of γ-CuBr single crystals. (May 2018) - Yue, Shuangqiang; Gu, Mu; Liu, Xiaolin; Li, Fengrui; Zhang, Juannan; Liu, Bo; Huang, Shiming; Ni, Chen
Graphical abstract: Highlights: Transparent γ-CuBr single crystal with regular shape was successfully grown by hydrothermal method. The x-ray excited optical luminescence of the γ-CuBr crystal, which exhibits an intensive 430 nm emission, is first reported. The average decay time of the 430 nm emission is 36.9 ns. Abstract: A fast scintillation crystal, γ-CuBr, was successfully grown by hydrothermal method with NH4 Br mineralizer. The element mole ratio of the Cu/Br crystal was about 0.91 caused by the crystal grown in a rich bromine environment. Under ultraviolet excitation, the crystal exhibited an intense 420 nm emission, a shoulder emission at 428 nm and a weak broadband emission at 560 nm, which could be related to free exciton recombination, Cu and Br vacancies, respectively. Furthermore, the X-ray excited optical luminescence of the crystal was first reported, and a strong 430 nm emission was observed. The analysis of luminescence decay kinetics revealed that the 430 nm emission is composed of two components with an average decay time of 36.9 ns. It means that the γ-CuBr crystal is a promising candidate for applications in fast radiation detection.